Improvement of mobility and stability for small electric vehicle : integration of oversteering characteristic, four wheel drive and independent steering - Muhammad Izhar, Ishak (2016)
Over the 20th century, increasing carbon dioxide emission by petroleum-based transportations is one of the main contributor to global warming. Moreover, escalation of global human population has put a pressure on the amount of carbon dioxide emission especially in developing countries rather than developed countries [ 1-1]. A research paper from the National Academy of Sciences of the USA concluded that climate change that takes place due to the global warming is largely irreversible for 1,000 years even after emissions of carbon dioxide stop [1-2]. This environmental issues by petroleum-based transportations along with the issue of fossil fuel depletion around the world have led activist and lobbyist to pressure automotive manufacturers to redesign future vehicles.